Stability of steel arches strengthened by textile membranes. (August 2021) - Machacek, Josef; Svoboda, Ondrej
Abstract: The stabilization effect of textile membranes on in-plane and out-of-plane stability of a steel arch supporting the membranes is investigated. Model of a large membrane structure using Ferrari ® Précontraint 702S fabric was tested in laboratory under various loadings and the resulting deflection/stress values are presented. The numerical model employed SOFiSTiK software and 3D geometrically nonlinear analysis with imperfections (3D GNIA). The model was validated comparing the results with the arch and membranes behavior at tests. The prime goal of the article is an extensive stability study of the large barrel-type textile roofs supported by a row of steel arches. The behavior of the both arches alone and those stabilized by the membranes is studied using geometrically nonlinear analysis (3D GNA) to design properly the supporting arches followed by linear buckling analysis (3D LBA) to find critical in-plane and out-of-plane loads in the form of buckling length factors. The study covers a variety of arch geometries, boundary conditions, membrane prestressings and loadings. The detailed analysis of buckling of arches alone resulted into refining of the buckling length factors currently used in standards. The summarized results of a wide spectrum of arches stabilized by membranes declare the decisive role of membranes for both in-plane and out-of-plane loss of the arch stability and may simply be used for a preliminary design of the supporting arches. Highlights: Detailed analysis of in-plane and out-of-plane buckling length factors of circle arches alone and those supporting barrel type membrane assemblies. Stabilizing effect of membranes on the supporting arch buckling length factors with respect to various aspect arch ratios (span vs rise). Analysis of peripheral membrane assembly supports (flexibility of outside arches) and their influence on the buckling length factors of the supporting arches.